(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article analyzes Ulugbek Hamdam’s work "Loneliness." The article artistically expresses a person’s inner experiences, mental anguish, and alienation from society. The work reveals loneliness in a person from a philosophical and psychological point of view, describes mental states characteristic of humanity through images.